Pengaruh Literasi Digital dan Kemandirian Belajar terhadap Kemampuan Berpikir Kritis dengan Penggunaan Artificial Intelligence Sebagai Variabel Moderasi - Audy Oktafiani; Khasan Setiaji (Universitas Cokroaminoto Palopo, 2025)
The rapid advancement of digital technology requires students to develop Digital Literacy and Learning Autonomy to adapt to modern learning dynamics and enhance their Critical Thinking Ability. This study aims to examine the impact of Digital Literacy and Learning Autonomy on students' Critical Thinking Ability, with Artificial Intelligence (AI) as a moderating variable. The research employed a quantitative approach using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, analyzed through SmartPLS 4.1 software. Data were collected through online questionnaires from 202 respondents selected via simple random sampling from the 2022 class of Economics Education students at the Faculty of Economics and Business, Universitas Negeri Semarang (FEB UNNES). The results indicate that both Digital Literacy and Learning Autonomy have a positive and significant effect on students’ Critical Thinking Ability. Furthermore, AI significantly and strongly moderates the relationship between Digital Literacy and Critical Thinking Ability (path coefficient β = 0.203; p = 0.010), but does not significantly moderate the relationship between Learning Autonomy and Critical Thinking Ability (path coefficient β = 0.051; p = 0.520). These findings suggest that students with higher levels of Digital Literacy are able to leverage AI tools more effectively to enhance their cognitive processes and analytical reasoning. Therefore, Digital Literacy and Learning Autonomy are essential in shaping students' Critical Thinking Ability, while the use of AI serves as a cognitive accelerator, particularly for those already possessing strong digital competence. This study contributes to the development of higher education by emphasizing the importance of integrating Digital Literacy and responsible AI usage in learning environments. Promoting these elements can foster independent learning and strengthen students' Critical Thinking Ability, preparing them to excel academically and professionally in the digital eraThe rapid advancement of digital technology requires students to develop Digital Literacy and Learning Autonomy to adapt to modern learning dynamics and enhance their Critical Thinking Ability. This study aims to examine the impact of Digital Literacy and Learning Autonomy on students' Critical Thinking Ability, with Artificial Intelligence (AI) as a moderating variable. The research employed a quantitative approach using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, analyzed through SmartPLS 4.1 software. Data were collected through online questionnaires from 202 respondents selected via simple random sampling from the 2022 class of Economics Education students at the Faculty of Economics and Business, Universitas Negeri Semarang (FEB UNNES). The results indicate that both Digital Literacy and Learning Autonomy have a positive and significant effect on students’ Critical Thinking Ability. Furthermore, AI significantly and strongly moderates the relationship between Digital Literacy and Critical Thinking Ability (path coefficient β = 0.203; p = 0.010), but does not significantly moderate the relationship between Learning Autonomy and Critical Thinking Ability (path coefficient β = 0.051; p = 0.520). These findings suggest that students with higher levels of Digital Literacy are able to leverage AI tools more effectively to enhance their cognitive processes and analytical reasoning. Therefore, Digital Literacy and Learning Autonomy are essential in shaping students' Critical Thinking Ability, while the use of AI serves as a cognitive accelerator, particularly for those already possessing strong digital competence. This study contributes to the development of higher education by emphasizing the importance of integrating Digital Literacy and responsible AI usage in learning environments. Promoting these elements can foster independent learning and strengthen students' Critical Thinking Ability, preparing them to excel academically and professionally in the digital era.